2020
DOI: 10.2147/idr.s241073
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence of Virulence Genes and Their Association with Antimicrobial Resistance Among Pathogenic <em>E. coli</em> Isolated from Egyptian Patients with Different Clinical Infections</p>

Abstract: Introduction: Escherichia (E.) coli can cause intestinal and extra-intestinal infections which ranged from mild to life-threatening infections. The severity of infection is a product of many factors including virulence properties and antimicrobial resistance. Objectives: To determine the antibiotic resistance pattern, the distribution of virulence factors and their association with one another and with some selected resistance genes. Methods: Virulence properties were analyzed phenotypically while antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 68 publications
3
46
3
Order By: Relevance
“…By contrast, a positive correlation has been shown between AMR and virulence with the use of other antibiotics. In particular, uropathogenic strains of E. coli carrying the blaCTX-M-15 resistance gene also harbored more colV, colE2-E9, colIa-Ib, hlyA, and csgA genes as well as the blaOXA-2 beta lactamase was correlated with increased expression of colM, colB, colE, and crl genes [44]. Prophages are another mechanism that has been shown to be involved in both virulence and resistance diffusion through the spread of toxins to other resistant strains [45].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, a positive correlation has been shown between AMR and virulence with the use of other antibiotics. In particular, uropathogenic strains of E. coli carrying the blaCTX-M-15 resistance gene also harbored more colV, colE2-E9, colIa-Ib, hlyA, and csgA genes as well as the blaOXA-2 beta lactamase was correlated with increased expression of colM, colB, colE, and crl genes [44]. Prophages are another mechanism that has been shown to be involved in both virulence and resistance diffusion through the spread of toxins to other resistant strains [45].…”
Section: Discussionmentioning
confidence: 99%
“…UPEC strains carrying the bla CTX-M15 presented more colV , colE2-E9 , colIa-Ib , hlyA , and csgA genes. On the other hand, some UPEC strains present bla OXA-2 beta lactamase together with presence of colM, colB, colE , and crl genes [ 28 ]. It has been reported that tetA and tetB positive E. coli strains more often carry the virulence factors for P- fimbriae and aerobactin than susceptible strains [ 29 ].…”
Section: Relationship Between Antibiotic Resistance and Virulence mentioning
confidence: 99%
“…In addition to the above-mentioned properties, IncF plasmids also possessed virulence genes which can contribute to the fitness of bacterial clones inside mammalian hosts. For example, the traT gene related to serum resistance was found on every bla CTX-M -harboring IncF plasmid, except for IncF (F24:A-:B1), and this gene has been consistently associated with urinary tract infections and sepsis in humans (71)(72)(73)(74). Similarly, hlyF (hemolysin), iutA (iron uptake), and ompT (outer membrane protease) genes present on some of the bla CTX-M -IncF plasmids are very commonly found in avian pathogenic E. coli (75).…”
Section: Fig 7 Legend (Continued)mentioning
confidence: 99%